تقييم جودة الفحص الضريبي في ظل قانون ضريبة الدخل رقم (24) وتعديلاته في سورية (دراسة ميدانية على مديريات المال في الساحل السوري) - الضابط, مدين إبراهيم (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يعد انخفاض الحصيلة الضريبية والارتفاع المهم في معدل التهرب الضريبي، وانخفاض قدرتها على تمويل متطلبات الإنفاق العام المتزايد، من المشكلات المهمة التي يعاني منها النظام الضريبي السوري. وباعتبار أن الفحص الضريبي هو من أهم الوظائف التي تقوم بها الإدارة الضريبية، للتحقق من مدى صحة الالتزامات الضريبية التي يصرح عنها المكلفون، فإن مدى جودته يحدد بشكل كبير مستوى قدرتها على تأمين الموارد الضريبية. يهدف هذا البحث التعرف على الفحص الضريبي بوصفه مفهوماً وإجراءات في ظل قانون ضريبة الدخل رقم /24/ لعام 2003 وتعديلاته، والوسائل المعتمدة التي تضمن جودته في حال وجودها. كما يهدف إلى قياس تلك الجودة، بالاعتماد على معايير يتم تطبيقها في نظم ضريبية أخرى، إذا ما تم التأكد من خلو النظام الضريبي السوري من تلك الوسائل. وقد أظهرت نتائج هذا البحث عدم توافر هذه الوسائل بالفعل، الأمر الذي فرض إجراء عملية القياس باستخدام معايير رقابة الجودة بوصفها إحدى تلك الوسائل المعتمدة في أنظمة ضريبية أخرى. وأفضت إلى أن عملية الفحص الضريبي لا تتم بالجودة المطلوبة. وعليه، فقد أوصت الدراسة بضرورة تبني تلك الوسائل من جهة، وتبني مقترحات بتطبيق معايير رقابة الجودة من شأنها أن تحسّن جودة الفحص الضريبي في ضوء عملية التقييم التي تم القيام بها، من جهة أخرى. The decrease in the tax revenues, as a result of the significant increase in the rate of tax evasion that causes a decline in their abilities to finance the requirements of public spending growing, is considered one of the crucial problems that affect the tax system in Syria. As well-known, the examination of the tax is one of the most important functions carried out by the tax administration to verify the validity of the tax liabilities which are disclosed by the taxpayers. Thus, the extent of the examination quality determines their abilities to secure the tax resources. This research aims to identify the tax examination as a concept and procedures under the Income Tax Law No. / 24 / of 2003, and the means, if any, that have been adopted and used to ensure that the tax examination performing meets the quality requirements. Also, it aims to measure the tax examination based on quality standards, as one of these means, which are applied in other tax systems. These will be done, if these means are not found in Syrian tax system. The results of this research showed that these means are not available in the tax system in Syria. Which forces a measurement process by using the quality control standards, as one of these means, that had been adopted in other tax systems. The results of measurement showed that the tax examination performing does not meet the quality requirements. The study recommends the need to adopt these means, and the proposals to apply the quality control standards that will improve the quality of the tax examination in the light of the evaluation process that has been done.